ANALISIS KONFLIK PENDIRIAN SANGGAR KEROHANIAN SAPTA DARMA DI REMBANG - Arnis Rachmadhani (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
The destruction of Sanggar Candi Busono (Sapta Dharma) in Rembang, Central Java in 2015 has shown a disharmony relationship between the adherents of Sapta Darma and those who refused it. This article describes the results of conflict analysis through the elements of conflict and chronological analysis of the vandalism of Sanggar Candi Busono (Sapta Dharma) in Blandok, Plawangan Village, Kragan Rembang. This study uses descriptive analysis method of qualitative data collected through interviews, observations, and document review. The findings of this study are that the construction of Sanggar Candi Busono (Sapta Dharma) becomes a trigger for unharmonious relationship between adherents of Sapta Darma and the local residents. Besides there are differences in reference to the regulations by the two parties in which the Sapta Darma referred to the Joint Regulations of Minister of Home Affairs and Minister of Culture and Tourism No. 43 of 2009 and No. 41 of 2009. While the religious scholars, community leaders and Blandok pleople rejected on the basis of Joint Regulations of the Minister of Religious Affairs and Minister of Home Affairs No. 9 of 2006 and No. 8 of 2006. The chronological conflict also denoted that the Rembang government has initiated conflict resolution effort by issuing the regulations of the use of Sanggar Candi Busono only for meeting activities but not functioned as a place of worship. It can be also used as a learning center for the followers of Sapta Darma and community in Blandok and surrounding areas.